Pulsed electric field assisted process for extraction of bioactive compounds from custard apple (Annona squamosa) leaves - Khursheed Ahmad Shiekh; Oladipupo Odunayo Olatunde; Bin Zhang; Nurul Huda; Soottawat Benjakul (Elsevier Ltd., 2021)
Impact of pulsed electric field (PEF) assisted process on preparation of custard apple leaf extract (CALE) using ethanol (70%, v/v) was studied. Different electric field strengths (2–6 kV/cm), pulse numbers (100–300 pulses) with specific energies (45–142 kJ/kg) for 2.5 to 5 min were implemented. Cell disintegration index was higher in CALE when PEF 6 kV/cm, 300 pulses, 142 kJ/kg for 5 min was applied. Extraction yield was higher (+5.2%) than the untreated counterpart (13.28%). Chlorophyll A and B contents were negligible in PEF pre-treated CALE. PEF improved radical scavenging activities assessed by DPPH, ABTS radical scavening activities and FRAP. The antibacterial properties of CALE against Staphylococcus aureus and Escherichia coli were highest. Purpureacin 2 and rutin were abundant in PEF pre-treated CALE. Therefore PEF was the potential aid in augmenting extraction yield and bioactivities of the extract from custard apple leaves.